Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/aje/kwx328
|View full text |Cite
|
Sign up to set email alerts
|

Relative Validity of Nutrient Intakes Assessed by Questionnaire, 24-Hour Recalls, and Diet Records as Compared With Urinary Recovery and Plasma Concentration Biomarkers: Findings for Women

Abstract: We evaluated the performance of a semiquantitative food frequency questionnaire (SFFQ), the Automated Self-Administered 24-Hour Dietary Recall (ASA24), and 7-day dietary records (7DDRs), in comparison with biomarkers, in the estimation of nutrient intakes among 627 women in the Women's Lifestyle Validation Study (United States, 2010-2012). Two paper SFFQs, 1 Web-based SFFQ, 4 ASA24s (beta version), 2 7DDRs, 4 24-hour urine samples, 1 doubly labeled water measurement (repeated among 76 participants), and 2 fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(173 citation statements)
references
References 50 publications
2
158
2
Order By: Relevance
“…Third, the potential effect of long-term blood storage on the biomarker stability might lead to nondifferential measurement errors and likely attenuate the observed associations in this study. However, the questionnaires used in the current study were highly validated against multiple types of information, including diet records and biomarkers (26,27,44). In addition, the consistency of our results with other previous experimental and population-based studies suggests that the observed associations were unlikely to be entirely explained by residual confounding or measurement errors.…”
Section: Discussionsupporting
confidence: 74%
“…Third, the potential effect of long-term blood storage on the biomarker stability might lead to nondifferential measurement errors and likely attenuate the observed associations in this study. However, the questionnaires used in the current study were highly validated against multiple types of information, including diet records and biomarkers (26,27,44). In addition, the consistency of our results with other previous experimental and population-based studies suggests that the observed associations were unlikely to be entirely explained by residual confounding or measurement errors.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the higher risk groups were not mutually exclusive, except for women with prepregnancy obesity. While random errors in the dietary data are plausible, a validation study of the Willett food frequency questionnaire detected valid folate intake compared to biomarkers and 24‐hour recall assessment (Yuan et al, ). We believe differential recall of the dietary data is unlikely because most U.S. consumers have poor health literacy and are not aware of micronutrient levels in food (Persoskie, Hennessy, & Nelson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our prior analyses, regular aspirin use was defined as use of at least two standard tablets (325 mg) of aspirin per week . Dietary risk factors, including alcohol, processed red meat, folate, calcium and vitamin D, were assessed through FFQs as previously described . To account for the amount of carbohydrate in a typical serving, we derived a global dietary glycemic load (GL) score by multiplying the amount of carbohydrates in the diet by the average glycemic index (GI) .…”
Section: Methodsmentioning
confidence: 99%